Outcomes of Thoracic Endovascular Aortic Repair for Acute Type B Dissection in Patients With Intractable Pain or Refractory Hypertension. (April 2018) - Laquian, Liza; Scali, Salvatore T.; Beaver, Thomas M.; Kubilis, Paul; Beck, Adam W.; Giles, Kristina; Huber, Thomas S.; Feezor, Robert J.
Purpose: To compare uncomplicated acute type B aortic dissection (UATBAD) patients with intractable pain/refractory hypertension treated with thoracic endovascular aortic repair (TEVAR) to UATBAD subjects without these features receiving best medical therapy (BMT).Methods: Interrogation of the hospital database identified 101 consecutive UATBAD patients admitted between January 2011 and December 2014. Of these, 74 patients (mean age 62±13 years; 44 men) were treated with BMT; the other 27 UATBAD patients (mean age 63±13 years; 17 men) were subsequently treated with TEVAR for intractable pain (24, 89%) and/or refractory hypertension (3, 11%) at a mean 2.4±3.3 days (median 1, range 0–12) after admission. Mixed models were employed to determine differences in centerline measured aortic remodeling. Propensity analysis was employed to mitigate selection bias. Kaplan-Meier methodology was used to estimate reintervention and survival.Results: The groups were well matched; there was no difference in demographics, comorbidities, or proportion with visceral involvement (70% for TEVAR vs 86% for BMT, p=0.08). There was no significant difference in length of stay (9.6±6.3 for TEVAR vs 10.3±7.8 for BMT, p=0.3), complications (19% for TEVAR vs 24% for BMT, p=0.6), or 30-day mortality (0 for TEVAR vs 7% for BMT, p=0.1). One (4%) TEVAR patient experienced retrograde dissection. BMT resulted in greater mean increase in discharge antihypertensive medications (1.7±1.9 vs 0.7±1.7 for TEVAR, p=0.03), but there was no difference in narcotic utilization. Mean follow-up was greater in the TEVAR group (17.9±16.0 months) compared with BMT patients (11.5±10.8 months, p=0.05). TEVAR significantly improved rates of aortic diameter change (1.5% vs 12.9% for BMT, p=0.007), complete false lumen thrombosis (41% vs 11% for BMT, p=0.004), and true lumen expansion (85% vs 7% for BMT, p<0.01). However, there was no difference in reintervention (25.9% for TEVAR vs 23% for BMT, p=0.2) or survival (log-rank p=0.8).Conclusion: TEVAR for UATBAD with intractable pain/refractory hypertension is safe but offers no short-term outcome advantage when compared to UATBAD patients without these features receiving BMT. A significant improvement in aortic remodeling was identified after TEVAR. The potential long-term reintervention and aorta-related mortality benefits of this favorable remodeling have yet to be defined and randomized trials are warranted.